From Vision to Reality: A Holistic Examination of Transformational Leadership as a Catalyst for Cultivating Organizational Culture in Pesantren - Bashori, Bashori; Yusup, Muhammad; Khan, Razeev (Development: Studies in Educational Management and Leadership, 2022)
The focus of the study is the concept of transformational leadership and its influence on nurturing a strong and cohesive organizational culture within Pesantren. This article examines the key dimensions of transformational leadership and their role in cultivating a supportive environment that aligns with the vision and values of Pesantren through a comprehensive review of scholarly literature and empirical studies. The findings demonstrate the importance of visionary leadership, inspirational motivation, intellectual stimulation, and individualized consideration in fostering positive organizational culture change. In addition, this article proposes strategies and recommendations for Pesantren leaders to harness the potential of transformational leadership in order to establish a sustainable and flourishing organizational culture. This research contributes to the existing corpus of knowledge on leadership and organizational culture, particularly in the context of Pesantren, and offers educational leaders and policymakers valuable insights.